First scientific research on common bottlenose dolphins in the Calabrian (Italy) Ionian Sea - Maria Assunta Menniti; Adriana Vella; Jessica Alessi (Academia Biology)
Bottlenose dolphins (Tursiops truncatus) suffer from multiple anthropogenic pressures due to their habitat preference in coastal waters. As this vulnerable species is protected under the European Habitats Directive and various other conventions (Bern, Barcelona, Bonn) and agreements (ACCOBAMS), it requires MPAs (such as SCIs—Sites of Community Importance and SACs—Special Areas of Conservation) for their protection. Bottlenose dolphin research carried out in the stretch of the Southern Ionian Sea, between Brancaleone and Botricello, has reduced the gap in knowledge about the presence and distribution of cetacean species in this region. The first year-long study, in 2019, was developed through the regional operational program 2014–2020, 6.5.a.1-sub-action 2 “Conserving, restoring and protecting habitats and species of the Natura 2000”. The project involved a multi-action approach including scientific field research, citizen science in order to increase the knowledge and awareness regarding the marine environment and dolphins’ conservation, and removal of the marine litter in the SAC Fondali di Stalettì in order to reduce the negative impact these could have on the health of the bottlenose dolphins (entrapment in abandoned fishing ghost nets, plastic ingestion, etc.). Preliminary results on the presence and distribution of bottlenose dolphins scientifically investigated year-round are presented here. Similar scientific studies are necessary for cetacean protection providing necessary knowledge for the institution of marine protected areas (MPAs) and monitoring for effective conservation of marine mammals.